European and Mediterranean mercury modelling: Local and long-range contributions to the deposition flux. (September 2015) - Gencarelli, Christian N.; De Simone, Francesco; Hedgecock, Ian M.; Sprovieri, Francesca; Yang, Xin; Pirrone, Nicola
Abstract: Mercury (Hg) is a global pollutant that is known to have adverse effects on human health, and most human exposure to toxic methylmercury is through fish consumption. Soluble Hg compounds in the marine environment can be methylated in the water column and enter the base of the food chain. Atmospheric deposition is the most important pathway by which Hg enters marine ecosystems. The atmospheric chemistry of Hg has been simulated over Europe and the Mediterranean for the year 2009, using the WRF/Chem model and employing two different gas phase Hg oxidation mechanisms. The contributions to the marine deposition flux from dry deposition, synoptic scale wet deposition and convective wet deposition have been determined. The Hg deposition fluxes resulting from transcontinental transport and local/regional emission sources has been determined using both Br/BrO and O3 /OH atmospheric oxidation mechanisms. The two mechanisms give significantly different annual deposition fluxes (129 Mg and 266 Mg respectively) over the modelling domain. Dry deposition is more significant using the O3 /OH mechanism, while proportionally convective wet deposition is enhanced using the Br/BrO mechanism. The simulations using the Br/BrO oxidation compared best with observed Hg fluxes in precipitation. Local/regional Hg emissions have the most impact within the model domain during the summer. A comparison of simulations using the 2005 and 2010 AMAP/UNEP Hg emission inventories show that although there is a decrease of 33% in anthropogenic emissions between the two reference years, the total simulated deposition in the regions diminishes by only 12%. Simulations using the 2010 inventory reproduce observations somewhat better than those using the 2005 inventory for 2009. Highlights: Gas phase conversion of Hg 0 to Hg II by O3 /OH is not very consistent with observations. A Br/BrO oxidation mechanism compared best with observed Hg precipitation fluxes. Local emissions contribute most to the overall Hg deposition flux in the summer. Long-range transport of Hg contributes most to winter Hg deposition.